2019
DOI: 10.1007/s11307-019-01394-7
|View full text |Cite
|
Sign up to set email alerts
|

SPECT Imaging of Muscle Injury with [99mTc]MDP in a Mouse Model of Muscular Dystrophy

Abstract: Purpose: Tc-99m methylene diphosphonate ([ 99m Tc]MDP) is an in vivo bone imaging agent that also accumulates in injured skeletal muscle cells. The objective of this study was to investigate if [ 99m Tc]MDP could be used to detect muscle injury in the mdx mouse model of Duchenne muscular dystrophy (DMD). Procedures: Static whole-body single-photon emission computed tomography/computed tomography (CT) scans were acquired at 2 h post-injection of [ 99m Tc]MDP in two cohorts of animals at different sites: one coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…This consensus is oversimplified and a range of calcium salts may be observed including HAp, apatite, (amorphous) calcium phosphate, whitlockite, calcium oxalate and calcium carbonate 34 . Various studies have demonstrated the presence of calcification in a wide variety of diseases, including atherosclerosis 25 , 29 , 30 , age-related macular degeneration 35 , Alzheimer’s disease 36 , muscular dystrophy 23 , various cancers 21 , 37 , 38 , kidney stones 26 , 27 , 31 and chronic kidney disease (CKD) 39 .…”
Section: Introductionmentioning
confidence: 99%
“…This consensus is oversimplified and a range of calcium salts may be observed including HAp, apatite, (amorphous) calcium phosphate, whitlockite, calcium oxalate and calcium carbonate 34 . Various studies have demonstrated the presence of calcification in a wide variety of diseases, including atherosclerosis 25 , 29 , 30 , age-related macular degeneration 35 , Alzheimer’s disease 36 , muscular dystrophy 23 , various cancers 21 , 37 , 38 , kidney stones 26 , 27 , 31 and chronic kidney disease (CKD) 39 .…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of HAp in bones makes [ 18 F]NaF an excellent tracer for the imaging of bones. On the other hand, reports on the mineral composition of extraosseous calcification (EC), which is defined as "deposition of calcium in tissues outside of bone" [27] and includes conditions such as vascular calcification, are diverse and contradictory [28][29][30][31][32][33][34][35][36][37][38][39][40][41]. For example, often these calcifications are euphemistically called HAp as a blanket term for all forms of apatite or solid calciumcontaining mineral.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have demonstrated the presence of calcification in a wide variety of diseases, including atherosclerosis [32, 33, 37-39, 44, 45], age-related macular degeneration [46], Alzheimer's disease [47], muscular dystrophy [30], various cancers [28,[48][49][50][51][52][53][54][55][56], kidney stones [34,35,40,57] and chronic kidney disease (CKD) [58,59]. Nonetheless, [ 18 F]NaF is the only clinically used PET tracer for the imaging of extraosseous calcification [60].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Four types of NPs were used (Table 1, Fig. 1): the monoclonal antibody, TRASTUZUMAB (PLA/ MMT/TRA) modified with polylactic acetate (PLA) and montmorillonite (MMT), which specifically targets HER2 receptor extracellular domain 15 ; ethylene diamine N,N,N' ,N' tetramethylene phosphonic acid NPs coated with PLA (PLA/EDTMP) 16 , which are used in breast and bone cancer treatment; silicon NPs PLGA/MDP modified with methylene diphosphate (MDP) and coupled to poly lactic-co-glycolic acid (PLGA) 17 , which can be used in scintigraphy; and Pluronic F127 MICELLES (Pluronic F127 Ms), that can be administered dermally 18 , intranasally, or intravenously 19 . HUVEC-STs were used as a cellular model.…”
mentioning
confidence: 99%